Technology adoption by small-scale full-time and part-time family farm households in the subtropics of Jammu & Kashmir - Rajinder Peshin; Rakesh Sharma; Raj Kumar; Laxmi K Sharma; Sudhakar Dwivedi; Rakesh Nanda; Vinod Gupta; Kernel S Risam (Agricultural Economics Research Review, 2023)
This paper has assessed technology adoption and its impact on the agricultural productivity for small-scale full-time and part-time farm households in the subtropical region of Jammu & Kashmir (J&K). We find only 24% of the farm households being exclusively dependent on farming for their livelihoods. For the remaining households, agriculture is a secondary economic activity. They are engaged in nonfarm economic activities, and use more of external inputs, such as fertilizers and pesticides than do the fulltime farm households. The high-yielding varieties, irrigation, herbicides and nitrogenous fertilizers are identified as important determinants of crop yield.